Perceptions of care and family support from patients and family caregivers during the COVID-19 pandemic: a phenomenological study in Spain - Joana Maria Julià-Móra; Margarita Calafell-Vert; Francesca Rosa Rosal-Obrador; Ian Blanco-Mavillard; Margalida Miró-Bonet (BMC Nursing)
Abstract Background Since the declaration of the COVID-19 pandemic in March 2020 and throughout the health crisis, health authorities recommended restriction measures to minimize the risk of contagion and avoid the collapse of health centers. The restrictive health and safety measures conditioned the way in which patients were cared for, as well as their social and family life. The purpose of the study was to explore patients and caregivers’ perception of family care and support during hospitalization in the context of the COVID-19 pandemic in a Manacor hospital. Method From an interpretive phenomenological approach, data was collected through the first author’s field diary and 30 semi-structured interviews with patients and family caregivers. Thematic analysis was used to identify themes and subthemes, and rigor was achieved through multiple coding and systematic comparisons. Results The findings underscore the profound emotional toll that restrictive visitation policies during the pandemic took on patients and their family caregivers. Limited family support led to feelings of loneliness, isolation, and emotional distress among patients, exacerbating their vulnerability. Participants highlighted the critical role of family presence in improving emotional stability and physical recovery, hinting at the importance of fostering psychological resilience in healthcare settings. Additionally, the study revealed inconsistencies in the communication and dissemination of information, which aggravated stress and confusion among participants. Clear, consistent, and empathetic communication strategies were considered essential for patient care and satisfaction. Participants expressed gratitude toward healthcare professionals and advocated for a person-centered approach that addresses not only clinical, but also emotional and psychological needs. Conclusions The study highlights the need to improve care for vulnerable populations, such as those at the end of life, to ensure dignified and compassionate care. It also points at the importance of post-discharge support for patients recovering from serious illnesses. The findings provide valuable information to improve person-centered care and the communication of future healthcare protocols amid health crises such as COVID-19.